Dynamic analyses of operating offshore wind turbines including soil-structure interaction. (15th February 2018) - Zuo, Haoran; Bi, Kaiming; Hao, Hong
Highlights: The tower and blades are modelled in detail. The influence of operational conditions on the wind load is considered. Responses of wind turbine under different operational conditions are studied. The effects of SSI and rotor velocity are systematically investigated. Abstract: In the dynamic analyses of offshore wind turbines subjected to the external vibration sources, the wind turbines are normally assumed in the parked condition and the blades are considered by a lumped mass located at the top of the tower. In reality, the geometrical characteristics and rotational velocity of the blades can directly influence the wind loads acting on the blades. Moreover, the centrifugal stiffness generated by the rotating blades can increase the stiffness and natural frequencies of the blades, which in turn can further affect the structural responses. The lumped mass model, therefore, may lead to inaccurate structural response estimations. On the other hand, monopile, a long hollow steel member inserting into the water and sea bed, is generally designed as the foundation of an offshore wind turbine. The soil-monopile interaction can further alter the vibration characteristics and dynamic responses of offshore wind turbines. In the present study, the dynamic responses of the modern NREL 5 MW wind turbine subjected to the combined wind and sea wave loadings are numerically investigated by using the finite element code ABAQUS. The blades are explicitly modelled and soil-structure interaction (SSI) is considered. The influences of operational condition and rotor velocity on the dynamic behaviours are systematically investigated. It is found that the responses of the wind turbine in the operating condition are much larger than those in the parked condition; SSI can affect the tower vibrations substantially, while it has a negligible effect on the in-plane vibrations of the blades.